Analisis Kepercayaan dan Pengetahuan Produk Cash Waqf Link Deposit pada Minat Nasabah - Risna Hairani Sitompul; Fadillah Harahap (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2026)
This study aims to analyze customers' interest in using the Cash Waqf Linked Deposit (CWLD) product and to identify the influence of trust and knowledge on their interest at PT. Bank Sumut Syariah Padangsidimpuan. This research employed a qualitative method with a descriptive approach. Data were collected through interviews with the Customer Service officer as the primary informant and supported by documentation. Data analysis consisted of data reduction, data presentation, and conclusion drawing, while data validity was ensured through source triangulation. The findings indicate that customers' interest in the CWLD product is relatively good, as reflected in their attraction, confidence, and willingness to participate. Customers' interest is influenced by trust, which is reflected in the institution's reliability, employees' competence, and service quality, as well as by knowledge, which is shaped by educational background, access to information, and the social, cultural, and economic conditions of the community.